(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes issues related to reforms in the judicial and legal system during the period of independence. It emphasizes several stages of reforms implemented in the judicial and legal sphere of Uzbekistan during the years of independence and highlights the importance of justice-related matters. The principles of transparency and accessibility of justice for all, as well as issues pertaining to public involvement, are also discussed.